Alcohol‐Related, Drug‐Related, and Non–Substance‐Related Aggression: 3 Facets of a Single Construct or 3 Distinct Constructs?. (6th August 2020) - Chester, David S.; Bucholz, Kathleen K.; Chan, Grace; Kamarajan, Chella; Pandey, Ashwini K.; Wetherill, Leah; Kramer, John R.; Nurnberger, John I.; Salvatore, Jessica E.; Dick, Danielle M.
Abstract : Background: Aggression often occurs alongside alcohol and drug misuse. However, it is not clear whether the latent and manifest relations among alcohol‐related, drug‐related, and non–substance‐related aggression are separate manifestations of a single construct or instead are 3 distinct constructs. Methods: To examine these associations, we conducted a preregistered analysis of 13, 490 participants in the Collaborative Study on the Genetics of Alcoholism. In a structured interview, participants reported their lifetime perpetration of these 3 aggression phenotypes. Results: The data were better fit by a model that treated these aggression phenotypes as 3 distinct latent factors, as compared to models in which the items all loaded onto 1 ("general") or 2 ("substance‐related" and "non–substance‐related") aggression factors. This 3‐factor model fit better for men than women. Subsequent exploratory analyses then showed that among these 3 factors, alcohol‐related aggression explained the variance of overall aggression better than the other 2 factors. Conclusions: Our findings suggest that these 3 forms of aggression are distinct phenotypes (especially among men). Yet, people's alcohol‐related aggression can accurately characterize their overall aggressive tendencies across these domains. Future research will benefit from articulating the unique and shared pathways and risk factors underlying each of these facets of aggression. Abstract : This figure depicts the results of a factor analysis that shows how alcohol‐related aggression (ARA), drug‐related aggression (DRA), and non‐substance‐related aggression (NSRA) are best modeled as distinct constructs, instead of reflecting a general aggressive tendency.